Longitudinal trajectories of BMI z‐score: an international comparison of 11, 513 Australian, American and German/Austrian/Luxembourgian youth with type 1 diabetes. Issue 2 (5th November 2019) - Phelan, Helen; Foster, Nicole C.; Schwandt, Anke; Couper, Jennifer J.; Willi, Steven; Kroschwald, Peter; Jones, Timothy W.; Wu, Mengdi; Steigleder‐Schweiger, Claudia; Craig, Maria E.; Maahs, David M.; Prinz, Nicole; et al.
Summary: Background: BMI fluctuations during puberty are common. Data on individual change in BMI from childhood to young adulthood are limited in youth with type 1 diabetes. Objectives: To compare longitudinal trajectories of body mass index z score (BMIz) from childhood to adolescence across three registries spanning five countries. Methods: Data sources: T1DX (USA), DPV (Germany/Austria/Luxembourg) and ADDN (Australia). The analysis included 11, 513 youth with type 1 diabetes, duration > 1 year, at least one BMI measure at baseline (age 8‐10 years) and > 5 aggregated BMI measures by year of age during follow‐up until age 17 years. BMIz was calculated based on WHO charts. Latent class growth modelling was used to identify subgroups following a similar trajectory of BMIz over time. Results: Five distinct trajectories of BMIz were present in the T1DX and ADDN cohorts, while six trajectories were identified in the DPV cohort. Boys followed more often a low/near‐normal pattern while elevated BMIz curves were more likely in girls (ADDN; DPV). For T1DX cohort, no sex differences were observed. Comparing the reference group (BMIz 0) with the other groups during puberty, higher BMIz was significantly associated with older age at T1D onset, racial/ethnic minority and elevated HbA1c (all p<0.05). Conclusion: This multinational study presents unique BMIz trajectories in youth with T1D across three continents. The prevalence of overweight and the longitudinal persistence of overweight support the need for close monitoring of weight and nutrition in this population. The international and individual differences likely result from diverse genetic, environmental and therapeutic factors.